"Fantastic Charities": The Transformation of Waqf Practice in Colonial Zanzibar - Oberauer, Norbert (Islamic law and society, 2008)
Abstract The present study examines the impact of British colonial rule on waqf practice in Zanzibar. I argue that colonial policy towards waqf did not aim at the dismantlement of waqf as such. Nonetheless, it disrupted traditional patterns of waqf practice. Traditionally, waqf was controlled by wealthy patron families who used endowments to foster bonds of dependence and loyalty with manifold clientele and to maintain mosques representing the patron's social status. This practice was antithetical to British political and economic ideas, which were modern and capitalist. British officials insisted that patrons must use their wealth as a business resource and that the maintenance of mosques was a responsibility of the state. Accordingly, the British controlled waqf administration classified endowments as either "family waqf" or "mosque waqf". The first was fully exploited in favour of the founder's family, while the latter was turned into revenue for public mosque upkeep. As a result, waqf ceased to be an economic base for patron-client relationships and clients were transformed into a modern working class entirely dependent on wage labour.